On the stability of a finite difference scheme with two weights for wave equation with nonlocal conditions - Novickij, Jurij; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2014)
We consider the stability of a ﬁnite diﬀerence scheme with two weight param-eters for a hyperbolic equation with nonlocal integral boundary conditions. We obtain stability region in the complex plane by investigating the characteristic equation of a diﬀerence scheme using the root criterion.The research was partially supported by the Lithuanian State Science and Studies Foundation, grant MIP-047/2014.
Keywords: integral conditions; hyperbolic equation; weighted diﬀerence scheme; stability region